Identification of Students' Online Learning Readiness (KBO) in the Post-Pandemic Period - Darmiany Darmiany; Muhammad Erfan; Mohammad Archi Maulyda (Jurnal Penelitian Pendidikan IPA, 2023)
Â  This study aims to identify online learning readiness (KBO) students of FKIP University of Mataram. This type of research is quantitative with a descriptive approach. The study used a KBO questionnaire instrument which was compiled with a scoring system. Analysis of the data used is the Pearson product moment correlation to see the correlation between KBO scores and academic abilities possessed by students. The results showed that students' online learning readiness (KBO) was at a score of less than 80, meaning that students' online learning readiness was still not very good. Meanwhile, according to the Pearson product moment correlation data analysis, it shows that the student correlation value from JIP is 0.815. For students from JMIPA it is 0.10. Meanwhile, students from JPBI and JIPS got a correlation value of 0.386 and 0.59. Based on these data, it can be concluded that JIP and JIPS students have a strong correlation between academic ability and students' KBO scores. While JMIPA and JPBI, students' academic ability and KBO scores have a low level of correlation.